KINERJA PRAMUSAJI DI RESTORAN ALICE HOTEL THE LANGHAM JAKARTA - Achmadi, Rudhi; Putri Nofanda, Dama Divya; Widiarto, Setyo (STABN Raden Wijaya Wonogiri, 2023)
The objective of this study is to assess the quality of service or performance at Alice Restaurant within Alice Hotel The Langham Jakarta, specifically with regards to five service quality indicators: tangibles, reliability, responsiveness, empathy, and assurance. This research follows a descriptive quantitative approach, involving a total of 60 respondents. Data collection was conducted through the distribution of questionnaires. The findings of this study indicate that, when assessing the overall service quality at Alice The Langham Jakarta using the Importance-Performance Analysis (IPA) method, a conformity level of 101% is achieved. This implies that the performance has surpassed guest expectations, signifying a high degree of satisfaction. Notably, there are two points in quadrant A on the Cartesian diagram that warrant particular attention, as their performance slightly falls short of expectations.